2023
DOI: 10.3389/fendo.2023.1147554
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine regulation of GnRH neuronal activity: A circuit in the medial septum

Abstract: In vertebrates, gonadotropin-releasing hormone (GnRH)-secreting neurons control fertility by regulating gonadotrophs in the anterior pituitary. While it is known that acetylcholine (ACh) influences GnRH secretion, whether the effect is direct or indirect, and the specific ACh receptor (AChR) subtype(s) involved remain unclear. Here, we determined 1) whether ACh can modulate GnRH cellular activity and 2) a source of ACh afferents contacting GnRH neurons. Calcium imaging was used to assay GnRH neuronal activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 78 publications
4
14
1
Order By: Relevance
“…The carbachol-triggered decrease in the frequency of mPSCs after the inward current was blocked by atropine indicates the involvement of mAChRs in this process. Previous reports have also shown mAChR-dependent ion currents in goldfish (Kawai et al, 2013) and embryonic mouse GnRH neurons (Shostak et al, 2023).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The carbachol-triggered decrease in the frequency of mPSCs after the inward current was blocked by atropine indicates the involvement of mAChRs in this process. Previous reports have also shown mAChR-dependent ion currents in goldfish (Kawai et al, 2013) and embryonic mouse GnRH neurons (Shostak et al, 2023).…”
Section: Discussionmentioning
confidence: 76%
“…Our work also revealed the subunit compositions of nAChRs; the presence of α3β4, α4β2 and α7 receptors was confirmed in GnRH neurons, of which the α3β4 and the α4β2 were localized in the same GnRH neuron. The hypothalamic presence of functional α4β2 and α7 receptors has previously been demonstrated with the major role of α7 (Huang et al, 2011) and the expression of α3 subunit shown in embryonic GnRH neurons (Shostak et al, 2023). Interestingly, the α4, α7, β2 and β4 subunits were not found in these embryonic neurons, indicating different nAChR signaling in adult versus embryonic GnRH neurons.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations